The Structural Types of the Polarization Detection Unit in Imaging Polarimeter Based on the Stokes Parameter Method - Yuanhao Li; Xiaohan Guo; Kai Zhang; Xiaoyang Li; Fang Kong; Ziying Jia (Sensors, 2025)
Bio-inspired imaging polarimeters have significant applications in the field of detecting the polarization state of skylights. The polarization detection principle of polarization detection units in polarimeters is mostly based on the Stokes parameter method. Using the Stokes parameter method, multiple linearly polarized lights modulated by the incident light need to be obtained. According to the polarization modulation method of the polarization detection unit, imaging polarimeters can be classified into time-division types, channel-division types, and division of focal-plane types. Different from the classification in previous studies, this review divides channel-division polarimeters into single-sensor channel-division and multi-sensor channel-division polarimeters, avoiding the confusion of concepts between aperture-sharing polarimeters and amplitude-sharing polarimeters in previous classifications. This review introduces the different ways of achieving polarization-state imaging through various bionic imaging polarimeters and expands on the advanced polarization detection unit structure design technologies based on the Stokes parameter method introduced in recent years, aiming to provide inspiration for bio-inspired imaging polarimeters used in navigation and positioning.